Gandhi, De Quincey and Hali: The pleasures and pains of opium. Issue 1 (May 2020) - Majeed, Javed
This essay explores Gandhi's representations of opium as indicative of the addictive nature of the colonial relationship in India. It also shows how the opium trade had an impact on Gandhi's redefinition of food. Some submissions to the 1893–94 Royal Commission on Opium in India refer to De Quincey and reading De Quincey's Confessions alongside Gandhi's Hind Swaraj and Guide to Health reveals how both authors grappled with questions of dependency and selfhood in relation to modernity. I also discuss Gandhi's representations of pleasure and opium alongside Altaf Hussain Hali's (1837–1914), whom Gandhi admired as a reformist Urdu poet. Opium and intoxicants were a site on which colonial and postcolonial agency were both imagined and compromised in Gandhi, De Quincey and Hali.